2021
DOI: 10.1128/msphere.00991-20
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Seasonal Anoxia on the Microbial Community Structure in Demosponges in a Marine Lake in Lough Hyne, Ireland

Abstract: Climate change is expanding marine oxygen minimum zones (OMZs), while anthropogenic nutrient input depletes oxygen concentrations locally. The effects of deoxygenation on animals are generally detrimental; however, some sponges (Porifera) exhibit hypoxic and anoxic tolerance through currently unknown mechanisms. Sponges harbor highly specific microbiomes, which can include microbes with anaerobic capabilities. Sponge-microbe symbioses must also have persisted through multiple anoxic/hypoxic periods throughout … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
32
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(33 citation statements)
references
References 139 publications
(176 reference statements)
1
32
0
Order By: Relevance
“…Some sponges can live in anoxic conditions for several months, such as the sponges of the family Raspailidae found in the deeper cliffs of Lough Hyne (Bell & Barnes, 2000; McAllen et al, 2009; Micaroni et al, 2021). Schuster et al (2021) suggested that this tolerance could be conferred by specific bacterial symbionts, which are able to carry out anaerobic metabolism. In addition, these sponges living in anoxia are all thin crusts, with a very high surface‐to‐volume ratio, which could favour the exchange of gases and the release of metabolic waste (Levin et al, 1991).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Some sponges can live in anoxic conditions for several months, such as the sponges of the family Raspailidae found in the deeper cliffs of Lough Hyne (Bell & Barnes, 2000; McAllen et al, 2009; Micaroni et al, 2021). Schuster et al (2021) suggested that this tolerance could be conferred by specific bacterial symbionts, which are able to carry out anaerobic metabolism. In addition, these sponges living in anoxia are all thin crusts, with a very high surface‐to‐volume ratio, which could favour the exchange of gases and the release of metabolic waste (Levin et al, 1991).…”
Section: Discussionmentioning
confidence: 99%
“…Species‐specific phenotypic plasticity appears to help these organisms to overcome hypoxic events, and future research will need to elucidate the mechanisms behind these changes. This exceptional adaptive capacity of sponges could be derived from their ancient evolutionary origin and could confer sponges a competitive advantage in future deoxygenated oceans over other organisms (Mills et al, 2014; Schuster et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, sponges have diverse and complex microbiomes and are classified as either "highmicrobial-abundance" (HMA) or "low-microbial-abundance" (LMA) based on their bacterial cell densities. As sponges lack essential components of the HIF oxygen-sensing pathway (Mills et al, 2018), it has been suggested that hypoxia and anoxia (zero oxygen) tolerance may be conferred to sponges via metabolic interactions with their microbiome (Schuster et al, 2021). In the laboratory, all sponges analyzed to date-with the exception of G. barretti-are most likely LMA sponges.…”
mentioning
confidence: 99%
“…One-way permutational analysis of variance (PERMANOVA) was used to test for overall differences in functional profiles among MAGs belonging to different taxonomic orders. To determine COG functions that contributed most to the dissimilarity between MAGs at the order level, similarity percentage analysis (SIMPER) was performed in PAST v 3.25 [84]. The top ten most differentiating COG functions were then plotted as vectors on the PCA diagram to explore relationships between gene functions and symbiont taxonomy.…”
Section: Data Analyses and Statisticsmentioning
confidence: 99%